2016
DOI: 10.3126/jssn.v19i1.24549
|View full text |Cite
|
Sign up to set email alerts
|

Comparision of ultrasonographic diagnosis with ‘Tzanakis’ Score in acute appendicitis

Abstract: Introduction: Acute appendicitis is one of the most common acute surgical abdominal conditions requiring surgery. Ever since the inflamed appendix was demonstrated in the 1980’s by Ultrasonography, it has been used as an aid to clinically diagnose acute appendicitis. Tzanakis scoring system is a combination of clinical examination, Ultrasonography and inflammatory markers. Methods: A retrospective non-randomized observational study was conducted from April 2014 to March 2015 on all cases of acute appendi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…1 Clinical examination is helpful in diagnosis of acute appendicitis in only 70 to 87% of the cases. 4 About 20% to 33% of patients with suspected acute appendicitis have atypical findings making clinical diagnosis difficult which requires plasma markers and imaging techniques. 5,6 Due to this overlap of symptoms, the rate of negative appendectomy has been reported to range from 20% to 40%.…”
Section: Introductionmentioning
confidence: 99%
“…1 Clinical examination is helpful in diagnosis of acute appendicitis in only 70 to 87% of the cases. 4 About 20% to 33% of patients with suspected acute appendicitis have atypical findings making clinical diagnosis difficult which requires plasma markers and imaging techniques. 5,6 Due to this overlap of symptoms, the rate of negative appendectomy has been reported to range from 20% to 40%.…”
Section: Introductionmentioning
confidence: 99%
“…By the application of this reliable Ultrasound-based score for diagnosing acute appendicitis, the process of decision making has improved, especially in developing countries lagging in resources. 6,7 In a recent study done in Pakistan, its sensitivity, specificity and overall diagnostic score was determined to be 99%, 91% and 95% respectively 8 indicating that it to be an accurate modality for - ----------------------------------------------------------------------------------------Received on 15-06-2021 Accepted on 25-10-2021 diagnosing of acute appendicitis and preventing a negative laparotomy in this region of the world. 9 However, a prospective study done in 2019 in India concluded that Tzanaki score is considering better diagnostic scoring system than Alvarado score for acute appendicitis 10 .…”
Section: Introductionmentioning
confidence: 99%